AN EFFICIENT MODEL FOR SUGARCANE YIELD PREDICTION - sumathi A (Journal of Global Pharma Technology, 2018)
Sugarcane is one of India's most basic renewable business crops. Yield prediction is one of the important problems in agricultural field. Data mining techniques are better choice to solve this problem. Using different data mining techniques increase the sugarcane yield performance.